Risk Factors of Symptomatic COVID-19 in Samtse District, Bhutan - Lhendup, Karma; Tsheten, Tsheten; Rinzin, Tshewang; Wangdi, Kinley (Frontiers in Public Health, 2022)
Introduction All COVID-19 positive cases in Samtse District, Bhutan were isolated in the Isolation facilities managed by the government hospitals. This study aimed to identify the socio-demographic risk factors for developing COVID-19 symptoms amongst these patients. Methods and Materials A secondary data of the COVID-19 positive cases from Isolation facilities of Samtse District from 5 May to 7 September 2021 was used for this study. Survival analysis was carried out to estimate the cumulative probability of symptom onset time by each risk factor. Kaplan-Meier curves were used to estimate the probabilities for the onset of symptoms at different time points and a log-rank test was employed to assess the differences between covariates. Results A total of 449 patients were included, of which 55.2% were males and 73.3% (328) were aged >18 years. The mean age was 42 years with the range of 3 months to 83 years. Forty-seven percent (213) reported at least one symptom. Common symptoms were: fever (32.3%, 145), headache (31.6%, 142) and cough (30.1%, 135), respectively. Males were 64% less likely to be symptomatic than females (adjusted hazard ratio (aHR)=0.36, 95% confidence interval [CI] 0.183 – 0.917). Farmers (aHR=3.17, 95% CI 1.119 – 8.953), and drivers and loaders (aHR=3.18, 95% CI 1.029 – 9.834) were three times more likely to be symptomatic compared to housewives. Residents of Samtse sub-districts were 5 times more likely to be symptomatic than those living in other sub-districts (aHR=5.16, 95% CI 2.362 – 11.254). Conclusion The risk of developing symptoms was being male, farmer, drivers and loaders and resident of Samtse sub-district who had a higher probability of developing symptoms of COVID-19. These high-risk groups should be provided additional care when in isolation facilities. Keywords: COVID-19, Bhutan, symptomatic, risk factors, survival, analysis, Samtse District, quarantine